2020
DOI: 10.1038/s41526-020-00108-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactome of miRNAs and transcriptome of human umbilical cord endothelial cells exposed to short-term simulated microgravity

Abstract: Adaptation of humans in low gravity conditions is a matter of utmost importance when efforts are on to a gigantic leap in human space expeditions for tourism and formation of space colonies. In this connection, cardiovascular adaptation in low gravity is a critical component of human space exploration. Deep high-throughput sequencing approach allowed us to analyze the miRNA and mRNA expression profiles in human umbilical cord vein endothelial cells (HUVEC), cultured under gravity (G), and stimulated microgravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…These included TGF-β signaling. Similarly, a group evaluating the effect of simulated microgravity on human umbilical cord endothelial cells found that microgravity altered the expression of miRNAs involved in cell proliferation, cell cycle regulation, TGF-β signaling, VEGF signaling, MAPK signaling, Jak-STAT signaling, focal adhesion, and wound healing [73].…”
Section: Discussionmentioning
confidence: 99%
“…These included TGF-β signaling. Similarly, a group evaluating the effect of simulated microgravity on human umbilical cord endothelial cells found that microgravity altered the expression of miRNAs involved in cell proliferation, cell cycle regulation, TGF-β signaling, VEGF signaling, MAPK signaling, Jak-STAT signaling, focal adhesion, and wound healing [73].…”
Section: Discussionmentioning
confidence: 99%
“…While the events and mechanisms controlling wound healing are well known and characterized, the pharmacological interventions to prevent or treat healing dysfunction are few and nowadays still under evaluation and validation on Earth. The data available in relation to unloading conditions document that the impaired wound healing results from the following mechanisms: 1) persistent inflammation with neutrophil infiltration ( Dovi et al, 2003 ; Radek et al, 2008 ) and overall alteration of the inflammatory phase; 2) altered blood flow with more permeable vessels ( McDonald et al, 1992 ), presumably linked to increased NO and VEGF levels ( Shi et al, 2012 ; Dittrich et al, 2018 ); 3) an altered neovascularization that may result from impaired EC proliferation and migration in response to angiogenic factors, increased EC apoptosis, and altered gene expression and signalling pathways ( Morbidelli et al, 2005 ; Radek et al, 2008 ; Li et al, 2018 ; Kasiviswanathan et al, 2020 ); 4) exposure to simulated microgravity also resulting in enhanced ROS production that may contribute to unloading-induced oxidative stress. The systemic oxidative status can be derived from radiation-induced immune system alterations especially relevant in long-duration space flight ( Rizzo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Examples are tissue engineering, cocultures, 3D multicellular structures, lab-on-chip approaches ( Grimm et al, 2014 ; Ma et al, 2014 ; Huang et al, 2020 ), which are starting to substitute experimental animals due to ethical issues. Thorough comprehension of the molecular and biochemical mechanisms underlying cellular responses is coming from omics techniques and RNA sequence analysis of samples from simulated and real microgravity experiments ( Ma et al, 2014 ; Mao et al, 2018 ; Cui et al, 2020 ; Kasiviswanathan et al, 2020 ). The expectations from these types of experiments are high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some microRNAs we identified to be activated in ARPE-19 cells cultured on board ISS are involved in cell response to spaceflight. Among them, hsa-miR-296 expression is affected in HUVEC cultured in a 3D clinostat to simulate microgravity, and it influences cell proliferation and vascular function in microgravity conditions [79]. hsa-miR-494 is upregulated in C2C12 myoblast cells subjected to clinorotation conditions and in osteoblasts isolated from tailsuspended rats, and this upregulation correlates with inhibition of osteoclast differentiation [80].…”
Section: Discussionmentioning
confidence: 99%